2014
DOI: 10.1590/1413-81232014196.08102013
|View full text |Cite
|
Sign up to set email alerts
|

Percepção da Aids pelos profissionais da saúde que vivenciaram a epidemia durante o cuidado prestado às pessoas com a doença, em Florianópolis (SC), Brasil (1986-2006)

Abstract: Percepção da Aids pelos profissionais da saúde que vivenciaram a epidemia durante o cuidado prestado às pessoas com a doença, em Florianópolis (SC), Brasil (1986Brasil ( -2006 Perception of AIDS among health professionals who experienced the epidemic while caring for people with the disease in Florianópolis in the state of Santa Catarina, Brazil (1986Brazil ( -2006

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
0
4
0
9
Order By: Relevance
“…Percebe-se também que o uso de tecnologias (conhecimentos/concepções teóricas, práticas, materiais) da época passou a ser questionado quanto à sua eficácia no enfretamento do surgimento da pandemia da Aids e/ou doenças que poderiam atingir os profissionais e proteger as pessoas atendidas nas instituições de saúde. Daí decorreu a busca por especializações de enfermagem (8,9).…”
Section: O Processo De Punção Venosa Periférica E Seus Recursos Tecnounclassified
See 2 more Smart Citations
“…Percebe-se também que o uso de tecnologias (conhecimentos/concepções teóricas, práticas, materiais) da época passou a ser questionado quanto à sua eficácia no enfretamento do surgimento da pandemia da Aids e/ou doenças que poderiam atingir os profissionais e proteger as pessoas atendidas nas instituições de saúde. Daí decorreu a busca por especializações de enfermagem (8,9).…”
Section: O Processo De Punção Venosa Periférica E Seus Recursos Tecnounclassified
“…O surgimento do(a) HIV/SIDA colocou em xeque valores, conhecimentos, práticas e hábitos utilizados pelos profissionais de saúde durante décadas por falta de conhecimentos científicos que alicerçassem as práticas laborais desenvolvidas por eles para lhes garantir segurança e também aos doentes (8,9) . Tal fato justifica a busca por um novo modelo de cuidado respaldado pela abordagem científica, capaz de fundamentar as práticas assistenciais que eram desenvolvidas (10) .…”
Section: O Processo De Punção Venosa Periférica E Seus Recursos Tecnounclassified
See 1 more Smart Citation
“…Data collection was using a validated tool that includes the identification of the original article, the methodological characteristics of the study and the evaluation of results found.1 1 Moreover, in the fourth stage, there was the categorization of studies on the subject of research (HIV/AIDS) and the SRT, which allowed the inference of three categories related to HIV/AIDS, to PVHA and health professional practices, discussed and contextualized as the convergence of aspects related to research in the thematic approach of social representations, constituting an integrative review.…”
Section: From This Perspective It Is Emphasized That Studies On Hiv/mentioning
confidence: 99%
“…he advent of HIV/AIDS and the high number of deaths at the beginning of the epidemic, have become an emerging public health problem in the world context 1 , which led to changes in organizational areas of health. The historical transformations related to HIV/AIDS epidemic occurred through new organization axis of civil society and interaction between collective needs and public policy achievements aimed at coping them.…”
mentioning
confidence: 99%